The impact of climate change on hospice and palliative medicine: A scoping and narrative review - David Harris; Bhargavi Chekuri; Aldebra Schroll; Nisha Shah; Laadi Swende; Collins Uzuegbu; Pamela Young (Elsevier, 2024)
Introduction: Climate change's severe impact on human health is becoming increasingly evident, particularly for vulnerable populations with serious illnesses. Climate-related extreme weather events are expected to increase demand for hospice and palliative care due to rising respiratory illnesses, heat-related issues, waterborne diseases, and aggravated chronic conditions. Our scoping review aimed to investigate the existing literature on climate change's impact on hospice and palliative medicine (HPM). Methods: We conducted a comprehensive literature search across various databases (e.g., Medline, EMbase, Web of Science, and Cochrane) using predefined climate change and HPM terms, resulting in 382 records. Following predetermined inclusion and exclusion criteria, 44 articles were selected for full-text review, and 20 were included for final analysis. In light of the limited literature on climate change's impact on HPM, we also sought narratives from HPM practitioners from across the world on their experiences in a changing climate. Results: Six major themes emerged: 1) The impact of climate change on HPM in low-income countries; 2) Descriptive pieces on climate change, climate disasters, and HPM; 3) Morbidity and mortality after climate disasters in the seriously ill population; 4) Discussion of euthanasia during climate disasters; 5) Recommendations and frameworks for disaster response in the field of HPM; 6) Carbon footprint of hospices. Additionally, narratives from HPM practitioners highlighted the disruptive effects of climate disasters on seriously ill patients and their caregivers as disasters caused care interruptions, reduced access to crucial health infrastructure, exacerbations of illness, accelerated disease progression, and increased morbidity and mortality. Conclusion: Existing research on climate change's impact on HPM is primarily anecdotal and descriptive, with a focus on climate-related disasters. Narratives from HPM practitioners worldwide underscore the disproportionate impact of climate disasters on seriously ill patients. Further research is necessary to comprehensively understand climate's intricate effects on HPM and to assess adaptable, mitigative, and resilient solutions against its adverse impacts.